Digital Media, Fake News and Pro-Movement for Democratic Change (MDC) Alliance Cyber-Propaganda during the 2018 Zimbabwe Election. Issue 4 (2nd October 2019) - Ncube, Lyton
ABSTRACT: Fake news and cyber-propaganda were ubiquitous in the mainstream and social media during the 30 July 2018 Zimbabwe election. Both the ruling Zimbabwe African National Union Patriotic Front (ZANU PF) party under Emmerson Mnangagwa and their nemesis the Movement for Democratic Change (MDC) Alliance under Nelson Chamisa resorted to "fake news" and cyber-propaganda warfare. However, there is a dearth of studies systematically engaging the subject. This article is qualitative. It utilises an interpretive approach to discuss thematic issues raised in purposively selected pro-MDC Alliance fake news and cyber-propaganda circulated on WhatsApp during the period under study and how these issues were articulated. The study demonstrates that the MDC's humorous cyber-propaganda largely focused on the Zimbabwe Electoral Commission (ZEC) and ZANU PF's alleged electoral shenanigans aimed at manipulating the "people's will". The intention was to delegitimise the electoral process, insinuating that any result announced by the ZEC not confirming a Nelson Chamisa victory would not be a true reflection of the people's will. This cyber-propaganda thrived largely because the ZEC and the Zimbabwe Broadcasting Corporation (ZBC) created an information vacuum by failing to give the nation regular updates after the voting process.